Analysis of Factors for Incomplete Informed Consent at Medical Record Installation of Bangil Regional General Hospital in 2021 - Mahbubah, Mahbubah; Roosalina, Arma; Holipah, Holipah (Fakultas Kedokteran Universitas Brawijaya, 2022)
All medical procedures on patients must be initiated by completing the informed consent. According to the hospital's minimum service standard, the completeness of informed consent filling is 100%, but the achievement of informed consent completeness at Bangil Regional General Hospital is still 37%. This study analyzed the causative factors of incomplete informed consent at Bangil General Hospital. The data analysis method used was descriptive. Data collection techniques were document studies and focus group discussions (FGD). Document studies were conducted on 100 informed consent documents, and FGD was done with 17 people consisting of 7 physicians-in-charge and 10 installation heads. The results of the FGD were analyzed using a fishbone diagram and revealed a list of problems that caused incomplete informed consent at Bangil General Hospital; then, scoring was carried out to determine the three main factors driving the problem of incomplete informed consent at the hospital. The three main factors for incomplete informed consent were the absence of a flow or policy guide for filling out, the unavailability of informed consent documents in outpatient installations, and the absence of a person in charge of the room for filling out informed consent.